Analyzing essential oils: extraction and characterization from fresh and dry leaves of Pinus elliottii - Deo, Leonardo Pratavieira; Aguiar Campolina, Gabriela; Oliveira, Cassia Duarte; Garcia, Kassy Jhones; Cardoso, Maria das Graças (Eclética Química, 2024)
Exploration of secondary metabolites, particularly essential oils, reveals diverse properties in antimicrobial, biological, and pharmaceutical contexts, including antibacterial, antifungal, and antiviral attributes, and applications in pest control and insect repellents. In the present work, essential oils were extracted from both fresh and dry leaves of Pinus elliottii, using hydrodistillation, followed by meticulous chemical characterization via gas chromatography coupled with a mass spectrometer. The plant leaves, sourced from a reforested area in the southern part of Minas Gerais, Brazil, formed the study's foundation. The main constituents identified in both essential oils were Germacrene D and β-Pinene. Germacrene D dominated in the essential oil from fresh foliage (47.71%), while β-Pinene prevailed in the essential oil from dry foliage (30.06%). Literature indicates that heightened Germacrene D levels may confer antibacterial and repellent properties, while elevated β-Pinene content aligns with various biological, medicinal, and pharmacological activities. Integrating our findings with existing literature, this work highlights potential applications for essential oils derived from both fresh and dry leaves of Pinus elliottii.